(untitled) (International Journal of Ayurveda and Pharma Research, 2017)
This study gives an understanding about the PTH mode of action as it accelerates the natural fracture healing process by shrinking callus size and increasing degree of mineralization of the fracture callus; thereby restoring intrinsic material properties. But, in human beings very few clinical research studies has been conducted with help of Hormonal parameters and its fluctuation during fracture healing with use of Ayurvedic formulation. Based on this, a random controlled study was conducted and fracture healing was assessed in the patients with simple and single fracture with assessment parameter hormone PTH (parathyroid hormone) and resulting values were statistically evaluated during fracture healing. treated group shows elevation pattern of serum hPTH so early initiation of bone resorption with early initiation of osteoblastic activity and continuous up to bone maturation so hardening of callus at fractured site may also quicker and this may helps to reduction in healing period or immobilization period and so early rehabilitation is possible.